EFFECT OF PUBLIC DEBT ON ECONOMIC GROWTH IN NIGERIA - Biliqees Ayoola ABDULMUMIN (Malete Journal of Accounting and Finance)
Public debt is a critical tool for governments to fund their spending, particularly when it is difficult to raise taxes and reduce public expenditure. However, this process has left most governments with massive outstanding debts, hence, the need to examine the effect of public debt on economic growth in Nigeria. The study employed secondary data, which was sourced from Central Bank of Nigeria Statistical bulletin over a period of 33 years from 1987 to 2020. The study adopted expost facto research design. The study also employed the Autoregressive distributive lag (ARDL). The result of the study revealed that external debt is a positive determinant of economic growth in Nigeria with a p-value of 0.0255. The study also revealed that domestic debt is a negative significant determinant of economic growth in Nigeria with a coefficient value of 0.0005. The study concludes that public debt has significant effect on economic growth in Nigeria. The study therefore recommends that government of Nigeria should make more use of external debt than domestic debt because of the low interest of external debt to domestic debt which will help in reducing the debt burden.